Seminary Formation: Recent History-Current Circumstances-New Directions - Schuth, Katarina (Asian Horizons, 2018)
Katarina Schuth, OSF, Seminary Formation: Recent History-Current Circumstances-New Directions, Collegeville, Minnesota: Liturgical Press, 2016. ISBN: 978-0-8146-4800-1. Pages: xx+191.